A sensitive and selective liquid chromatography mass spectrometry method for simultaneous estimation of anti-diabetic drugs inhibiting DPP-4 enzyme in human plasma: overcoming challenges associated with low recovery and sensitivity1. Issue 15 (7th August 2015) - Shantikumar, S.; Satheeshkumar, N.; Prasanth, B.; Lingesh, A.; Paul, David; Srinivas, R.
<x xml:space="preserve">Abstract</x> A simple and sensitive LC-QTOF/MS method was developed and validated to measure the human plasma concentrations of five gliptins.